LEGAL PRINCIPLES OF ORGANIC PRODUCTION IN UKRAINE: REALITIES AND PROSPECTS - Fedchyshyn, Dmytro; Ignatenko, Iryna; Shulga, Mykhaylo (Economics of Agriculture, 2018)
The purpose of the article is to consider the prospects of Ukraine concerning attraction of foreign investments into production of organic products. Formal-legal, materialist dialectics and comparative-legal methods are used. The attention is focused on the subjects of legal relations concerning organic production, in particular, on joint ventures with attraction of foreign capital, the stages of certification regarding the production of organic products. The temporary restrictions on the possession of agricultural land in some EU countries and in Ukraine have been analyzed. A comparative analysis of land lease institutions and the right to use anothers land for agricultural needs (emphyteusis) has been carried out.